Correlation between body mass index and gut concentrations of Lactobacillus reuteri, Bifidobacterium animalis, Methanobrevibacter smithii and Escherichia coli - MILLION, M; ANGELAKIS, E; MARANINCHI, M; HENRY, M; GIORGI, R; VALERO, R; VIALETTES, B; RAOULT, D (International Journal of Obesity, 2013)
Genus and species level analysis is the best way to characterize alterations in the human gut microbiota that are associated with obesity, because the clustering of obese and lean microbiotas increases with the taxonomic depth of the analysis. Bifidobacterium genus members have been associated with a lean status, whereas different Lactobacillus species are associated both with a lean and an obese status. We analyzed the fecal concentrations of Bacteroidetes, Firmicutes, Methanobrevibacter smithii, the genus Lactobacillus, five other Lactobacillus species previously linked with lean or obese populations, Escherichia coli and Bifidobacterium animalis in 263 individuals, including 134 obese, 38 overweight, 76 lean and 15 anorexic subjects to test for the correlation between bacterial concentration and body mass index (BMI). Of these subjects, 137 were used in our previous study. Firmicutes were found in >98.5%, Bacteroidetes in 67%, M. smithii in 64%, E. coli in 51%, Lactobacillus species between 17 and 25% and B. animalis in 11% of individuals. The fecal concentration of Lactobacillus reuteri was positively correlated with BMI (coefficient=0.85; 95% confidence interval (CI) 0.12-0.58; P=0.02) in agreement with what was reported for Lactobacillus sakei. As reported, B. animalis (coefficient=-0.84; 95% CI -1.61 to -0.07; P=0.03) and M. smithii (coefficient=-0.43, 95% CI -0.90 to 0.05; P=0.08) were negatively associated with the BMI. Unexpectedly, E. coli was found here for the first time to negatively correlate with the BMI (coefficient=-1.05; 95% CI -1.60 to -0.50; P<0.001). Our findings confirm the specificity of the obese microbiota and emphasize the correlation between the concentration of certain Lactobacillus species and obesity.